Energy, exergy, thermoeconomic and sustainability assessment of tire pyrolysis oil in common rail direct injection diesel engine. (1st March 2022) - Yaqoob, Haseeb; Teoh, Yew Heng; Jamil, Muhammad Ahmad; Sher, Farooq
Highlights: The energy, exergy, thermoeconomic, and sustainability analysis was conducted. Tire pyrolysis oil, biodiesel and diesel fuels were tested. DP10 (Diesel 90%-TPO 10%) shows the highest energy efficiency 37.12% at 3000 rpm. DP10 (Diesel 90%-TPO 10%) shows the highest exergy efficiency 39.60% at 3000 rpm. DP10 (Diesel 90%-TPO 10%) is the most sustainable fuel with the value of 1.65 sustainability index. Abstract: Waste to fuel conversion has attracted prominence due to higher fuel demand, waste disposal issues, and environmental and economic impact. Therefore, an alternative approach for addressing the issue of waste tire disposal can be provided by using tire pyrolysis oil (TPO). The energy, exergy, thermoeconomic and sustainability studies of TPO-diesel blends were carried out in this study. The analysis was compared with biodiesel-diesel blended fuel and pure diesel. DP10 (Diesel 90%-TPO 10%), DB10 (Diesel 90%-Biodiesel 10%), and neat diesel are used in the experimental study. The four-cylinder diesel engine was used to perform the experiments at different crankshaft speeds ranges 1000–3500 rpm with the increment of 500 rpm. The results reveal that at 3000 rpm, DP10 shows the highest energy and exergy efficiency, 37.12% and 39.60%, respectively, compared to DB10 and D100. The thermoeconomic study indicates that DP10 produced the lowest energy and exergy losses compared to DB10 and D100. The DP10 provides the highest sustainability index, demonstrating that the DP10 is the most sustainable fuel compared to D100 and DB10. It is concluded that the DP10 shows the best results, and it is appropriate to use in the turbocharged common-rail direct injection diesel engine.